Development an inventory of homosexuality and transgender exposure (IHTE): A Rasch analysis - Syahputra, Yuda; Sandjaja, Stefanus Soejanto; Afdal, Afdal; Ardi, Zadrian (Konselor, 2019)
The scientific interest in homosexual measurement has grown over the past 30 years, marked by new instruments and terms that have emerged. This condition is triggered by LGBT people who get justice, especially in westerly countries, so the instruments that emerge in westerly countries are more directed towards justice and development for LBGT people. For this reason, the existent instruments are not in accordance with the Indonesian State, because existent instruments have not been adjusted to godly and cultural values. The purpose of this study is to develop a valid and reliable Inventory of Homosexuality and Transgender Exposure (IHTE) in accordance with religious and cultural values in Indonesia. Research samples 304 people spread in 14 provinces in Indonesia. The sampling technique is done by purposive random sampling; the analysis technique used is Rasch model. The findings show that the IHTE instrument is valid and reliable, inventory development is discussed further.